Acute tibial tubercle avulsion fractures in children: selective use of the closed reduction and internal fixation method - Pesl, Tomas; Havranek, Petr (Journal of children's orthopaedics, 2008)
PURPOSE: Acute tibial tubercle avulsion fractures typically occur in adolescent boys involved in certain sports. All of the excerpted authors recommend open reduction and internal fixation (ORIF) as the only method to manage the displaced form of the injury. We attempted to select the optimal medical treatment of various types of this injury. The closed reduction and internal fixation (CRIF) method was selectively used. METHODS: During a period of 10 years (1997-2006), we treated 12 children with an acute injury to the tibial tubercle. Ogden's classification was used to describe the type of injury. Nine patients with a displaced fracture were treated surgically, using either the CRIF or ORIF methods. In cases of intraarticular fracture, the use of the CRIF method was tested. The suitability of the CRIF method was decided during manipulation of the fragments under an X-ray amplifier. RESULTS: According to Ogden's classification, three children were classified with type 1A, one with 1B, three with 2A, four with 3A, and one with 3B. In patients with the displaced extraarticular injury (types 1B and 2A), the ORIF method of treatment was necessary. In all but one case of intraarticular fracture (type 3A and 3B), the CRIF method was sufficient. CONCLUSIONS: The authors recommend that, for displaced intraarticular Ogden's type 3A or 3B fracture, the CRIF method should be considered as a first choice.